2014
DOI: 10.1093/ntr/ntu099
|View full text |Cite
|
Sign up to set email alerts
|

Early Quit Days Among Methadone-Maintained Smokers in a Smoking Cessation Trial

Abstract: introduction: Methadone maintenance treatment (MMT) patients have an exceedingly high prevalence of tobacco use, and interventions that have been specifically developed for this vulnerable subpopulation have struggled to attain even modest rates of cessation. A significant barrier has been an inability to initiate a quit attempt early in the treatment process and adherence to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…This may reflect inaccurate self-report of cigarettes smoked per day, or, alternately, proximity of cigarette smoking prior to research assessments. The limited tobacco abstinence we observed is consistent with data showing low rates of early tobacco cessation among smokers with substance use disorders (de Dios et al 2014; Nahvi et al 2014), and may be partially attributable to the short varenicline treatment course. Further, these tobacco abstinence rates are consistent with the modest cessation observed among smokers with opioid and other substance use disorders treated with varenicline (Nahvi et al 2014; Rohsenow et al 2017; Stein et al 2013).…”
Section: Discussionsupporting
confidence: 90%
“…This may reflect inaccurate self-report of cigarettes smoked per day, or, alternately, proximity of cigarette smoking prior to research assessments. The limited tobacco abstinence we observed is consistent with data showing low rates of early tobacco cessation among smokers with substance use disorders (de Dios et al 2014; Nahvi et al 2014), and may be partially attributable to the short varenicline treatment course. Further, these tobacco abstinence rates are consistent with the modest cessation observed among smokers with opioid and other substance use disorders treated with varenicline (Nahvi et al 2014; Rohsenow et al 2017; Stein et al 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Prior studies in the general smoker population, 30,31 as well as among opioid-dependent smokers, 16,[32][33][34] have shown that adherence to smoking cessation pharmacotherapies is highly correlated with abstinence. However, opioid-maintained patients have notoriously poor rates of adherence to non-opioid medications, 35,36 including smoking cessation medications.…”
Section: Support Medication Adherencementioning
confidence: 99%
“…Adherence to NRT, bupropion or varenicline is associated with improvement in smoking cessation outcomes [16][17][18][23][24][25][26][27][28][29][30][31][32][33], with a dose-dependent relationship between adherence and abstinence [19,25,32]. In large smoking cessation trials among smokers with OUD, adherence to cessation medications was associated with improved cessation outcomes [16,17,21,23,34]; in one trial there was a sevenfold odds of abstinence on days on which participants used (versus did not use) NRT [16]. These results highlight the critical importance of addressing adherence to achieve tobacco abstinence among smokers with OUD.…”
Section: Introductionmentioning
confidence: 99%